2021
DOI: 10.3389/fonc.2021.657191
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Survival Prediction of Patients With Acute Myeloblastic Leukemia Using Gene Expression Profiling

Abstract: Acute Myeloid Leukemia (AML) is a heterogeneous neoplasm characterized by cytogenetic and molecular alterations that drive patient prognosis. Currently established risk stratification guidelines show a moderate predictive accuracy, and newer tools that integrate multiple molecular variables have proven to provide better results. In this report, we aimed to create a new machine learning model of AML survival using gene expression data. We used gene expression data from two publicly available cohorts in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In AML, Wong et al demonstrated that KDM5B negatively regulates leukemogenesis in both mouse and human MLL-rearranged AML cells [ 47 ] through H3K4 demethylation, which leads to cell differentiation. Orgueira and colleagues used a computer learning algorithm termed ST-123 to predict survival of AML patients [ 48 ]. Their results suggest that, aside from age, expression of KDM5B and LAPTM4B are the strongest predictors of overall survival using multivariate cox regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In AML, Wong et al demonstrated that KDM5B negatively regulates leukemogenesis in both mouse and human MLL-rearranged AML cells [ 47 ] through H3K4 demethylation, which leads to cell differentiation. Orgueira and colleagues used a computer learning algorithm termed ST-123 to predict survival of AML patients [ 48 ]. Their results suggest that, aside from age, expression of KDM5B and LAPTM4B are the strongest predictors of overall survival using multivariate cox regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated the possibility to predict survival or response to intensive therapy using gene‐expression 18,48,60–63 . However, most of these studies do not account for major cofounding factors (such as treatment type and stem cell transplantation) or do not contain a validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the two previously published machine learning methods [ 12 , 13 ], our random forest model showed three main advantages. First, our random forest model was trained in the TCGA dataset and independently validated in the OHSU dataset, indicating a high reproducibility of survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the established model lacks independent validation [ 12 ]. Orgueira et al created a new machine learning model of AML survival using gene expression data and showed that the classifier achieved reasonable accuracy in predicting the survival rates of AML patients [ 13 ]. However, the accuracy of the classifier needs to be improved.…”
Section: Introductionmentioning
confidence: 99%